A Digital Thesaurus of Ethnic Groups in the Mekong River Basin - Chansanam, Wirapong; Kwiecien, Kanyarat; Buranarach, Marut; Tuamsuk, Kulthida (Informatics (Basel), 2021)
This research was aimed at constructing a thesaurus of the ethnic groups in the Mekong River Basin that is a compilation of controlled vocabularies of both Thai and English language, with a digital platform that enables semantic search and linked open data. The research method involved four steps: (1) organization of knowledge content; (2) construction of the thesaurus; (3) development of a digital thesaurus platform; and (4) evaluation. The concepts and theories used in the research comprised knowledge organization, thesaurus construction, digital platform development, and system evaluation. The tool for developing the digital thesaurus was the Tematres web application. The research results are: (1) there are 4273 principle words related to the ethnic groups that have been compiled and classified by the terms for each of the eight deep levels, 2596 were found to have hierarchical relationships, and 6858 had associative relationships; (2) the digital thesaurus platform was able to manage the controlled vocabularies related to the Mekong ethnic groups by storing both Thai and English vocabularies. When retrieved, the vocabulary, details of the broader term, narrow term, related term, cross reference, and scope note are displayed. Thus, semantic search is viable through applications, linked open data technology, and web services.